2014
DOI: 10.1155/2014/938532
|View full text |Cite
|
Sign up to set email alerts
|

Management of Injury to the Common Bile Duct in a Patient with Roux-en-Y Gastric Bypass

Abstract: Introduction. Most surgeons prefer Roux-en-Y hepaticojejunostomy (RYHJ) for biliary reconstruction following a common bile duct (CBD) injury. However, in patients with a Roux-en-Y gastric bypass (RYGB) a RYHJ may be technically challenging and can interfere with bowel physiology induced by RYGB. The use of a hepaticoduodenostomy (HD) resolves both these issues. Presentation of Case. We present a case of CBD injury during laparoscopic cholecystectomy one year after laparoscopic RYGB for morbid obesity. Due to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…There was a case report in a patient with similar features whose bypass was performed by open approach. 5…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was a case report in a patient with similar features whose bypass was performed by open approach. 5…”
Section: Discussionmentioning
confidence: 99%
“…However, laparoscopic cholecystectomy in this group of patients may result challenging due to the modified anatomy, postoperative adhesions and, frequently, the presence of a previous Roux-en-Y reconstruction. 5 We documented the successful case of a patient with story of non-supplemented laparoscopic gastric bypass, with subsequent injury of bile duct during a cholecystectomy and its repair. All these interventions were performed by minimally invasive surgery and a laparoscopic choledochoduodenal anastomosis was practiced.…”
Section: Introductionmentioning
confidence: 99%
“…The use of choledochoduodenostomy versus hepaticojejunostomy for recurrent CBD stones has been studied. Yaqub et al reported the case of a successful hepaticoduodenostomy (anastomosis between common hepatic duct above the cystic duct junction and the duodenum) following CBD injury in a patient with a history of RYGB [6] . Nonetheless, publications as early as the 1960s have suggested that for benign diseases choledochoduodenostomy should be considered only if there is no other alternative [7] , and a 1975 study published by Stefanini et al reported that over 20% of choledochoduodenostomies ultimately required conversion to formal hepaticojejunostomy [8] .…”
Section: Discussionmentioning
confidence: 99%